The Influence Of Service, Supervision, And Tax Sanctions On MSME Taxpayer Compliance With Tax Administration Digitalization As A Moderating Variable - Adiatma Adiatma; Waluyo Waluyo (UNIVED Press, 2025)
This study analyzes the influence of tax services, tax supervision, and tax sanctions on SME taxpayer compliance, with tax administration digitalization as a moderating variable. Using a quantitative approach, data were collected through questionnaires distributed to SME taxpayers registered at KPP Pratama Jakarta Cengkareng. Analysis using SmartPLS version 4 indicates that tax supervision and tax sanctions significantly affect SME taxpayer compliance. Tax supervision yielded a t-statistic of 2.543 (p-value 0.011), while tax sanctions had a t-statistic of 3.648 (p-value 0.000), confirming their crucial role in enhancing compliance. Conversely, tax services and tax administration digitalization showed no significant effect on compliance, with p-values of 0.872 and 0.317, respectively. Moreover, tax administration digitalization did not moderate the relationship between tax supervision and tax sanctions on compliance, as indicated by p-values of 0.900 and 0.772. These findings highlight the importance of optimizing supervision and enforcing sanctions to improve SME taxpayer compliance. Although tax digitalization continues to advance, this study suggests that such efforts have not directly contributed to compliance. Therefore, tax policies should focus on strengthening supervisory mechanisms and regulatory enforcement to enhance SME tax compliance.